Case Report: HAVCR2 mutation-associated Hemophagocytic lymphohistiocytosis - Song, Deli; Wang, Jingshi; Zhang, Jia; Hu, Junxia; Wu, Chaofan; Wang, Zhao (Frontiers in Immunology, 2023)
Germline HAVCR2 mutation has been reported to be associated with subcutaneous panniculitis-like T-cell lymphoma (SPTCL) leading to Hemophagocytic lymphohistiocytosis (HLH). Several studies have indicated that HAVCR2 mutation can cause HLH even in the absence of lymphoma, though the exact mechanism remains unclear. In this article, we reported five cases of HAVCR2 mutation-associated HLH. Our analysis revealed an elevated level of IL-1RA in the serum of these patients. Furthermore, we investigated the potential mechanisms underlying HLH associated with HAVCR2 mutation based on changes in cytokine levels. Our findings suggest that HAVCR2 mutation may represent a distinct genetic defect underlying HLH, differing from traditional primary HLH.